Perceptive Body Image Distortion in Adolescent Anorexia Nervosa: Changes After Treatment - Dalhoff, Anke W.; Romero Frausto, Hugo; Romer, Georg; Wessing, Ida (Frontiers in Psychiatry, 2019)
One key symptom of anorexia nervosa (AN) is body image distortion (BID). For example, AN patients who are asked to perform body size estimation tasks tend to overestimate their body size; this is thought to indicate a distortion of the perceptive component of body image. Although BID is an important treatment objective, only few treatment approaches explicitly target body image, and even fewer target the perceptive component. Moreover, very little is known about how patients’ perceptive body image changes after treatment and related weight gain. Consequently, we investigated changes of the perceptive BID in adolescent AN patients at the beginning (T1) and the end (T2) of inpatient treatment using a body size estimation task. A total of 38 AN patients performed the test for Body Image Distortion in Children and Adolescents (BID-CA) within the first two weeks of inpatient treatment and at the end of treatment. The results were compared to 48 healthy control (HC) participants performing the same task once. At T1, AN patients overestimated their body size more than HC, i.e. a total overestimation of 33 % in AN patients vs. 11 % in HC. At T2, AN patients overestimated their arm size to the same degree that they did at TI, but overestimations for the thigh and waist were reduced, and their overestimations for the waist no longer differed from the HC group. Thus, after treatment, AN patients were partly able to more realistically estimate their body size. Several factors may have influenced the observed changes in body size estimation, including task repetition, deliberate adjustment, growing into their preexisting perceptive body image through weight gain, as well as targeted and non-specific psychotherapeutic treatment. In conclusion, the perceptive BID in adolescent AN patients is persistent but also modifiable. Although diverse factors presumably play a role in changing BID, these findings suggest that AN patients may benefit from targeted treatment of BID.